Problems of Legal Regulation of Robotics and Artificial Intelligence from the Psychological Perspective - Baranov, Pavel P. (2020)
The article analyzes the main problems and contradictions in the formation of legal regimes for the regulation of robotics, artificial intelligence and other innovative technologies of our time. The work content shows the unpreparedness of modern legal science and practice to conceptual and legal design, legal and technical development of the regulatory legal acts aimed at the legislative fixation and regulation of the processes of using artificial intelligence and robots in public relations, as well as definition of responsibility and appropriate protection modes of legitimate interests, rights, freedoms in the system of personality - society - state. The subject of this study is the resolution of these problems and contradictions, as well as the identification of directions for the formation of a legal framework for the regulation of modern innovative technologies and digital processes unfolding in the modern society. The authors distinguish and analyze two consecutive stages: 1) development and introduction of necessary changes in the existing branches of Russian law; 2) conceptual-legal and doctrinal-legal formulation of key development priorities, as well as creation of a new integrated branch of law - robotics law, which has an independent subject and method of legal regulation.